Caracterização do número cromossômico em espécies de odontostilbe e serrapinnus (characidae: cheirodontinae) da bacia do rio paraguai, brasil - Troy, Waldo Pinheiro; Pacheco, Érica Baleroni; Oliveira, Claudio de [UNESP]; Miyazawa, Carlos Suetoshi (Universidade Estadual de Ponta Grossa (UEPG), 2010)
Cheirodontinae constitutes a group of 17 genera and 55 species still poorly studied cytogenetically, being that most data available in the literature is for the Alto Paraná basin. In this study Odontostilbe pequira, Serrapinnus kriegi, Serrapinnus calliurus and Serrapinnus microdon from Alto Paraguay basin was characterized cytogenetically. The modal diploid number 2n=52 found for these species, as well as most of the data cited in the literature, is an evidence of a conservadorism in chromosome number for the group.

Cheirodontinae constitui um grupo de 17 gêneros e 55 espécies ainda pouco estudadas citogeneticamente, sendo que a maioria dos dados disponíveis na literatura é da bacia do Alto Paraná. No presente estudo são caracterizadas cromossomicamente as espécies Odontostilbe pequira, Serrapinnus kriegi, Serrapinnus calliurus e Serrapinnus microdon da bacia do Alto Paraguai. O número diplóide modal 2n=52 encontrado para estas espécies, bem como a maioria dos dados citados na literatura, evidencia um conservadorismo do número cromossômico para o grupo.
Chromosomic number characterization of odontostilbe and serrapinnus species (characidae: cheirodontinae) from paraguay river basin, brazil
Keywords: Cytotaxonomy; Karyotypic macrostructure; Pantanal; Citotaxonomia; Macroestrutura cariotípica; Pantanal